2016
DOI: 10.1007/jhep03(2016)061
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on scale separation in flux vacua

Abstract: We argue that the Maldacena-Nuñez no-go theorem excluding Minkowski and de Sitter vacua in flux compactifications can be extended to anti-de Sitter (AdS) vacua for which the Kaluza-Klein scale is parametrically smaller than the AdS length scale. In the absence of negative tension sources, scale-separated AdS vacua are ruled out in 11-dimensional supergravity; in 10-dimensional supergravity, we show that such vacua can only arise in conjunction with large dilaton gradients. As a practical application of this ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(147 citation statements)
references
References 31 publications
10
130
0
Order By: Relevance
“…While the equations derived here agree with those of [] (for instance for p=6, we get false|scriptR6/scriptR4false|<O(1) as there), the interpretation of the result differs. We consider here that the separation of scale should be defined by a large hierarchy between the 4d scale and the internal typical scale L , defined e.g.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…While the equations derived here agree with those of [] (for instance for p=6, we get false|scriptR6/scriptR4false|<O(1) as there), the interpretation of the result differs. We consider here that the separation of scale should be defined by a large hierarchy between the 4d scale and the internal typical scale L , defined e.g.…”
supporting
confidence: 66%
“…by the volume; we have in mind that the internal Kaluza–Klein energy scale, defined by the (square root of the) first eigenvalue of the Laplacian on scalar fields, should be close to 1/L. On the contrary, the internal scale compared to the 4d scale in [] is defined by the average of false|scriptR6false|; the authors also specify that if this scale is different than the Kaluza–Klein scale, their analysis does not apply. We believe that for manifolds admitting the desired internal hierarchy, i.e.…”
mentioning
confidence: 99%
“…• Another work studying the resolution of the O6-plane singularities is [15]. There, it was argued that AdS solutions of type II (or 11d) supergravity cannot have scale separation unless they have explicit O-plane sources or large integrated dilaton gradients.…”
Section: The Exact Solutionsmentioning
confidence: 99%
“…11 Since the regular solution found in [11] has no explicit O-planes and an almost constant dilaton, [15] concluded that it cannot appear in vacua with scale separation such as the DGKT vacua. However, as we will discuss in more detail in Section 6, the argument of [15] is based on two assumptions about the KK scale which do not hold in general (and are indeed violated in the DGKT vacua). We therefore believe that the argument does not imply that a solution with resolved O-plane singularities would require large dilaton gradients.…”
Section: The Exact Solutionsmentioning
confidence: 99%
See 1 more Smart Citation